Nuclear Imaging in Infective Endocarditis - Nidaa Mikail; Fabien Hyafil (MDPI AG, 2021)
Infective endocarditis (IE) is a life-threatening disease with stable prevalence despite prophylactic, diagnostic, and therapeutic advances. In parallel to the growing number of cardiac devices implanted, the number of patients developing IE on prosthetic valves and cardiac implanted electronic device (CIED) is increasing at a rapid pace. The diagnosis of IE is particularly challenging, and currently relies on the Duke-Li modified classification, which include clinical, microbiological, and imaging criteria. While echocardiography remains the first line imaging technique, especially in native valve endocarditis, the incremental value of two nuclear imaging techniques, 18F-fluorodeoxyglucose positron emission tomography with computed tomography (18F-FDG-PET/CT) and white blood cells single photon emission tomography with computed tomography (WBC-SPECT), has emerged for the management of prosthetic valve and CIED IE. In this review, we will summarize the procedures for image acquisition, discuss the role of 18F-FDG-PET/CT and WBC-SPECT imaging in different clinical situations of IE, and review the respective diagnostic performance of these nuclear imaging techniques and their integration into the diagnostic algorithm for patients with a suspicion of IE.